Unwrapping the Emporium: Hudson’s Bay Company and the Legacy of Department Store Management in the Global Culture of Retailing - Rosebush, Emily (My University, 2021)
Between the 1850s to the 1960s, the department store emerged as a prominent retail format worldwide. As a retail format, the department store model broke away from pre-existing retailer and consumer conceptions of shopping and the shopping environment. Store leaders placed their focus on creating an uplifting mode of consumerism that perpetuated the department store as an ‘experience.’ However, behind the department store’s ‘magical’ façade, store management preplanned and manipulated consumer interactions with every part of the store. The managerial techniques managers used allowed these institutions to become an epicentre of consumerism and urban culture globally. The department store has lost its reputation as a vibrant shopping location in the digital age, and retailers and consumers alike have disregarded it as solely a monument of retail nostalgia. Nonetheless, today’s retailers still have much to learn from the ways department store leaders innovated. The management techniques used in department stores can provide insight into these institutions’ successes and pitfalls when navigating changing retail circumstances. If the department store is used as a tool of managerial know-how for retailers in the digital age, it could allow other retailers to sustain a semblance of the department store’s longevity, commercially and culturally. Hudson’s Bay, a remaining store in the Canadian department store industry, features as a case study to highlight the extent to which department store leaders designed and managed their stores.
Keywords: Canadian History; Transnational History; Department Stores; Consumerism and Consumption; Globalization; Retailing and Retail History; Business History; Hudson's Bay Company (HBC); Branding and Marketing; Management History; Managerial Techniques; Internationalization; E-commerce; Nationalism; Corporate Identity